Early central blood pressure elevation in adult patients with 21-hydroxylase deficiency. Issue 1 (January 2019) - Rosenbaum, David; Gallo, Antonio; Lethielleux, Gaelle; Bruckert, Eric; Levy, Bernard I.; Tanguy, Marie Laure; Dulon, Jérôme; Dahmoune, Nora; Salem, Joe Elie; Bittar, Randa; Leban, Monique; Girerd, Xavier; et al.
Abstract : Context: Controversial data exist on cardiovascular damages in patients with congenital adrenal hyperplasia (CAH). Objective: To assess blood pressure and early cardiovascular damages on a large cohort of adult CAH patients and control individuals. Design: Case–control study. Setting: Referral Center for Rare Disease, Pitié Salpêtrière Hospital, Paris, France. Patients or other participants: Fifty-eight women and 26 men with CAH diagnosed in childhood and 85 controls matched-paired for sex, age and smoking status were prospectively included. Intervention: Measurement of large arteries and microcirculatory anatomical and functional indices as well as hormonal status and cardiovascular risk factors evaluation. Main outcome measure: The primary objective was to compare carotid intima–media thickness (cIMT) in CAH patients and controls. The secondary objectives were to compare blood pressure (BP), radial augmentation index (rAI), central BP, carotid–femoral pulse wave velocity (PWV), skin microcirculation indices and inflammation parameters in CAH patients and controls. Results: Although PWV and cIMT were identical in patients and controls, higher rAI (64.6 ± 1.7 vs. 59.9 ± 1.6%, P  = 0.02) and higher central SBP (101.8 ± 1.5 vs. 95.1 ± 1.5 mmHg, P  < 0.001) were observed in CAH patients. Regarding microcirculatory indices, there was a higher functional resting capacity and a lower anatomical capillary density in CAH patients. In multivariate analysis, we found an independant association between CAH and central SBP elevation. Conclusion: We found an early rise in central SBP in CAH patients whereas sublinical arterial damages markers were normal. Our study suggest that vascular damages and increased cardiovascular risk could be mainly BP-driven. Abstract : Supplemental Digital Content is available in the text